2018
DOI: 10.1017/s2045796018000252
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and persistence of ADHD drug use in Japan

Abstract: Utilization of stimulants and atomoxetine for attention-deficit/hyperactivity disorder among 5.4 million children using population-based longitudinal data. Basic & Clinical Pharmacology &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
(30 reference statements)
1
7
1
Order By: Relevance
“…OROS methylphenidate was the most frequently prescribed medication in this study. This result was consistent with a retrospective cohort study using the National Database of Health Insurance Claim Information, in which the percentage of methylphenidate use among ADHD medication users was 64% in Japan [ 19 ]. Considering that methylphenidate is the most frequently used medication in children with ADHD in the UK (94%; [ 20 ]), Norway (94%; [ 21 ]), and Germany (75%–100%; [ 22 ]), the finding of 73.1% in this study is not high.…”
Section: Discussionsupporting
confidence: 90%
“…OROS methylphenidate was the most frequently prescribed medication in this study. This result was consistent with a retrospective cohort study using the National Database of Health Insurance Claim Information, in which the percentage of methylphenidate use among ADHD medication users was 64% in Japan [ 19 ]. Considering that methylphenidate is the most frequently used medication in children with ADHD in the UK (94%; [ 20 ]), Norway (94%; [ 21 ]), and Germany (75%–100%; [ 22 ]), the finding of 73.1% in this study is not high.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study assessing usage of ADHD drugs in Japan reported that among child and adolescent prevalent users of ADHD medications, approximately 64% were prescribed MPH and 41% were prescribed atomoxetine during 2014 19 . These proportions are different from those reported here, likely because guanfacine was approved in Japan after the study by Okumura et al was done, and because the present study included adult patients.…”
Section: Discussioncontrasting
confidence: 70%
“…The trend for a gradual increase in prescription rates is similar to that of other countries 26 29 . However, the prevalence of ADHD drug use in pediatric patients was lower in Japan (0.4%) 30 than in Norway and the United States (1.4–5.3%) 31 , 32 but similar to that in Italy, France, and the UK (0.2–0.5%) 33 35 . In addition, the share of OROS-MPH in 2014 is lower in Japan (64%) 30 than in Germany, the UK, and Norway (75–100%) 32 , 33 , 36 .…”
Section: Discussionmentioning
confidence: 76%